please solve

Asked by gober45 | 13th Feb, 2009, 05:28: PM

Expert Answer:

l tan θ + m sec θ = n .....(1)     l' tan θ - m' sec θ = n'........(2)

mltiply 1 with m'  and 2 with m and add we get sec θ term cancelled out and tan θ = (nm' + mn') / (lm' + ml')

similaly multiply 1 with l' and 2 with l and subtract tan θ cancelled out and we have sec θ =  (nl' - ln') / (ml' + lm')

we knoe 1 + tan 2 θ = sec 2 θ  so put the value get the answer

Answered by  | 13th Feb, 2009, 07:20: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.